Mechanism and experimental study on the fruit detachment of Chinese wolfberry through reciprocating vibration - Mei, Song; Wang, Jinpeng; Song, Zhiyu; Tang, Dunbing; Shen, Cheng (International Journal of Agricultural and Biological Engineering, 2024)
In order to realize the efficient and high-quality mechanical picking for Chinese wolfberry, firstly, the forcedreciprocating vibration picking principle of the Chinese wolfberry branch was studied, and the mechanical model of vibrationpicking was established based on the simplified cantilever model, and the response analysis and solution of all positions for thebranch were carried out. At the same time, the critical mechanical model of fruit detachment under the condition of fruithanging on branches was established, and the theoretical values of inertia force for each component of the branch wereobtained. Secondly, through actual measurement and finite element modeling, the natural frequency and forced vibrationresponse simulation for each component of the branch of Chinese wolfberry terminal branch model were both studied, and therelationship between single-point periodic excitation force and high-quality fruit shedding parameters was obtained. Thirdly,according to the conclusion of the picking model, a test bench with many groups of adjustable parameters was built. Finally, thelast branch of fruit-hanging Chinese wolf berry for Ningqi No.1 was taken as the experimental object, a four-level orthogonalexperiment was designed with three factors: frequency, amplitude and entrance angle. Meanwhile, the net picking rate, damagerate and false picking rate were taken as the evaluating indicators, referring to the comprehensive scores of the three factors. Itwas concluded that the primary and secondary relations of factors affecting the picking effect are frequency, amplitude andentrance angle, and the best operation parameters are frequency of 20 Hz, amplitude of 15 mm, and entrance angle of 45°, then,a hand-held vibration picker with setting parameters was trial-produced, and the optimal parameter combination was verified inthe Chinese wolfberry planting base of the National Chinese wolfberry Engineering and Technology Research Center. Theresults showed that the net picking rate of ripe Chinese wolfberry was 96.13%, the damage rate of fruit was 1.13%, and thefalse picking rate was 3.23%, mechanized picking efficiency was 30.28 kg/h, which is 6.65 times that of manual picking. Theexperimental results are consistent with the simulation results. The research results can provide an important basis for thecreation and operation standards of large-scale Chinese wolfberry vibration harvesting equipment. Keywords: Chinese wolfberry branches, reciprocating vibration, inertial force, orthogonal experiment DOI: 10.25165/j.ijabe.20241702.8482 Citation: Mei S, Wang J P, Song Z Y, Tang D B, Shen C. Mechanism and experimental study on the fruit detachment ofChinese wolfberry through reciprocating vibration. Int J Agric & Biol Eng, 2024; 17(2): 47–58.